TUMORAL AND NON TUMORAL PITUITARY LESIONS AND REPRODUCTIVE SYSTEM - I. A. Ilovayskaya (Acta Biomedica Scientifica)
Activity of reproductive system is under the hypothalamic and hypophysial control, defining role in development and normal functioning of gonads is played by impulsive secretion of GnRH and gonadotropins. The congenital genetic defects leading to the central hypogonadism can be found at any level of a hypotalamo-hypophysial axis: from disturbance of secretion of GnRH to structural defects of gonadotropins. The majority of cases are sporadic though various ways of inheritance have also been reported. The acquired hypotalamo-hypophysial disturbances can be organic and functional. Organic disorders of such lesion include different types of tumors localized at chiasmo-sellar region (first of all, pituitary tumors), consequences of surgical or radial intervention concerning these neoplasms, brain injuries and also autoimmune, infiltrative and other more rare species of diseases. Functional neuroendocrine disturbances arise against absence of visible changes of structure of a brain as the main reasons consider superfluous exercise stresses, stresses and critical depression of mass of a body